A review of nateglinide in the management of patients with type 2 diabetes - Tentolouris, Nicholas (Dove Medical Press, 2007)
Impaired insulin secretion occurs early in the pathogenesis of type 2 diabetes mellitus (T2DM) and is chronic and progressive, resulting initially in impaired glucose tolerance (IGT) and eventually in T2DM. As most patients with T2DM have both insulin resistance and insulin deficiency, therapy for T2DM should aim to control not only fasting, but also postprandial plasma glucose levels. While oral glucose-lowering treatment with metformin and thiazolidinediones corrects fasting plasma glucose, these agents do not address the problem of mealtime glucose spikes that have been shown to trigger atherogenic processes. Nateglinide is a derivative of the amino acid D-phenylalanine, which acts directly on the pancreatic β-cells to stimulate insulin secretion. Nateglinide monotherapy controls significantly mealtime hyperglycemia and results in improved overall glycemic control in patients with T2DM by reducing glycosylated hemoglobin (Hb(A1c)) levels. The combination of nateglinide with insulin-sensitising agents, such as metformin and thiazolidinediones, targets both insulin deficiency and insulin resistance and results in reductions in Hb(A1c) that could not be achieved by monotherapy with other antidiabetic agents. In prediabetic subjects with IGT, nateglinide restores early insulin secretion and reduces postprandial hyperglycemia. Nateglinide has an excellent safety and tolerability profile and provides a lifetime flexibility that other antidiabetic agents could not accomplish. The aim of this review is to identify nateglinide as an effective “gate-keeper” in T2DM, since it restores early-phase insulin secretion and prevents mealtime glucose spikes throughout the day and to evaluate the results of ongoing research into its potential role in delaying the progression to overt diabetes and reducing its complications and mortality.